Application of scanning electron microscopy and MALDI-TOF MS in the exploration of the parasporal insecticidal crystals of Bacillus thuringiensis strains isolated from Qatar soil. (September 2022) - Al-Thani, Aldana; Ashfaq, Mohammad Yousaf; Al-Thani, Roda; Hassan, Zahoor Ul; Jaoua, Samir
Abstract: Bacillus thuringiensis ( Bt ) plays an important role in health and agriculture due to its insecticidal activities. In this study, six Bt strains isolated from Qatar soil were used to explore their crystals morphologies and δ-endotoxin profiles. Bipyramidal crystal producing strains exhibited the genes vip3Aa58, cry1Aa/Ac, cry2Ab, cry1Ba and cry1Ia, predicting toxicity against lepidopteran, dipteran and hemipteran insects. A local strain QBT474 showed a high δ-endotoxin production of 647.32 ± 8.49 × 10 −6  ng/cell compared to 359.259 ± 15.02 × 10 −6  ng/cell in reference HD1 strain. The scanning electron microscopy showed bipyramidal, cuboidal and spherical crystals among the strains. MALDI-TOF-MS crystal protein profile data allowed to evidence differences in Bt crystal proteins. This is a first report that MALDI-TOF could be used in differentiating Bt δ-endotoxins in the strains forming same crystal forms. This study also demonstrates that local Bt strains might be considered for the industrial production of biological insecticides. Graphical abstract: Unlabelled Image Highlights: Most of the local Bt strains produced both bipyramidal and cuboidal crystals. Bipyramidal crystal producing strains exhibited the insecticidal genes. A local strain QBT474 produced highest d-endotoxin concentration. MALDI showed dissimilar protein profiles for the strains with different crystals.